Coronary artery bypass graft vs. percutaneous coronary angioplasty: CABG on the rebound? - Taggart, D (2007)
PURPOSE OF REVIEW: To examine the benefits of coronary artery bypass grafting (CABG) against percutaneous coronary intervention (PCI) and particularly the use of drug-eluting stents (DES) in situations where CABG has traditionally been considered the most effective therapy on clinical and economic grounds. RECENT FINDINGS: Current studies reconfirm that CABG is still the best therapy in terms of improved survival and freedom from reintervention for most patients with proximal left anterior descending, multivessel and left main-stem coronary artery disease (CAD) and that these benefits are even greater in diabetic patients. Health economic analyses also confirm the cost-effectiveness of medical therapy and CABG but not PCI. Furthermore, several meta-analyses have shown that DES do not improve survival or freedom from myocardial infarction compared with bare metal stents, but increase the risk of stent thrombosis, with associated medical and financial implications for prolonged dual antiplatelet medication. SUMMARY: In view of the evidence in favour of CABG, this article questions the justifiability of some trials of PCI vs. CABG, especially in diabetic patients and those with left main-stem CAD, and exhorts the need for a multidisciplinary team approach to the management of CAD as a minimum standard of care.